INFLUÊNCIA DO ENXERTO DE MÚSCULO ESQUELÉTICO NO PAVILHÃO AURICULAR NA REGENERAÇÃO MUSCULAR DE CAMUNDONGOS MDX - Leal, Anna Lúcia Rocha China (2006)
Duchenne Muscular Dystrophy (DMD) it is a fatal X-linked Xp21 locus inflammatory myopathy that affects 1 at 3500 male born neonates. Main clinical manifestation is muscular weakness, respiratory complications and evolution for death by the end of adolescence. Molecular alteration due to deletion and/or mutations in the dystrophin gene cause marked alteration in the cytoarchitecture of the muscular tissue. Dystrophin is a sarcolemmal protein that interacts with Factin in the sarcoplasm and laminin (LN) in the extracelular matrix. This promotes stabilization of the sarcolemma and protection against damage induced by the muscular contraction. Mdx mouse, a spontaneous mutant of the C57BL10/ScSn colony, is considered the appropriate animal model for studies of the physiopathology of DMD muscular lesion. Unlike the human homologous, mdx mice do not develop a fatal disease. Mdx mice show efficient regeneration and maintenance of muscular function throughout the life, though presenting characteristic phases with prevalence of myonecrosis, muscular regeneration and/or fibrosis. Experimental model of ectopic muscle grafting in the pina auricular allows detailed study of factors influencing cellular migration and inflammation in the implanted microenvironment and at distal sites. The aim of this study was to analyze the impact of grafting soleus muscle from C57 non dystrophic mice in the pina auricular of mdx mice in the microenvironment of the graft and the regeneration of skeletal muscles Triceps brachii (close site), Soleus and Gastrocnemius (distal site). Mdx mice at 6 weeks (w) received implant of 2w old Soleus muscle from C57 mice. Mdx mice, controls (C57/C57) and mdx mice submitted to surgical stress (sham) were sacrificed at 7, 10 and 15 days post grafting (dpe). The ears with implanted graft and also skeletal muscles (triceps, soleus and gastrocnemius) were processed for histology hematoxylin-eosin to assess morphological alterations. Tissues were also processed for imunohistochemistry to establish changes in the muscular microenvironment. It was used immunolabeling for Laminin (LN); NCAM positive cells for presence of satellite/activated myoblasts cells and hematopoietic stem cells (Sca-1+). Mdx 10dpe, showed increased expression of LN in the T.brachii (p <0,001), in the soleus (p <0,001) and gastrocnemius (p <0,01) skeletal muscles. Further increase of NCAM+ was also observed in skeletal muscles (T.brachii, Soleus) of mdx-Enx but not in the gastrocnemius muscles of mdx-Enx (15 dpe) and sham mdx mice. Likewise skeletal muscles of sham and mdx-Enx showed augment of Sca-1+ cells. Altogether the results indicate that implantation of ectopic syngeneic graft increased LN expression, proliferation and/or migration Sca-1+ cells into areas of muscular lesion further promoting muscle regeneration as assessed by increased numbers of NCAM positive cells in mdx muscles.